2017
DOI: 10.1140/epjd/e2017-70490-6
|View full text |Cite
|
Sign up to set email alerts
|

On the plasma confinement by acoustic resonance

Abstract: In an applied research project on the development of a pulsed microwave sulfur lamp prototype of 1 kW, we have discovered an amazing phenomenon in which the plasma forms a ball staying at the center of the bulb despite gravity, thus protecting the glass from melting. In this paper, it is shown that this results from an acoustic resonance in a spherical mode. Measurements of the plasma response to short pulses are presented showing beats at the spherical resonance. It is demonstrated that the beats could result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The current proposal is motivated by an observation made while studying acoustic plasma confinement [9,10]. As reported in [10], the 180 dB re 20 µPa sound wave that confines a lightly ionized collisional plasma causes luminosity oscillations in phase with its acoustic pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current proposal is motivated by an observation made while studying acoustic plasma confinement [9,10]. As reported in [10], the 180 dB re 20 µPa sound wave that confines a lightly ionized collisional plasma causes luminosity oscillations in phase with its acoustic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In this letter, we present a type of acoustic selfoscillation that may occur in an acoustic cavity filled with partially ionized gas located within a microwave cavity as shown in Figure 1. For the present analysis, the configuration is assumed similar to that found in [9][10][11], where the acoustic cavity was a sealed quartz sphere with a radius around 2 cm, and the surrounding microwave cavity was a thin-walled metallic cavity with a resonance near 2.45 GHz. Future implementations may include a means to couple the sound out of the acoustic cavity, for example by attaching a horn shaped outlet.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, research on high-powered sulfur lamps revealed that sound waves could drive hot gas to ball up in the center of the bulbs [2]. The surprising phenomenon caught the attention of Seth Putterman's acoustic group at the University of California, Los Angeles.…”
mentioning
confidence: 99%
“…al. [8][9][10] have recently observed the existence of acoustic modes inside the bulb that hold the hottest region of the plasma centrally, away from the glass. Their interest in these modes is motivated by a need to replace the mechanical rotation systems used in these lamps to distribute heat and suppress the formation of hotspots.…”
mentioning
confidence: 99%